Les vagabonds - Sarah VANUXEM (Journal of Interdisciplinary History of Ideas, 2023)
While vagrants enjoyed a place in society in the early Middle Ages, they lost it in modern times, and never regained it after the French Revolution. The institution of the offence of vagrancy accompanied the rise of industrial society, the development of capitalism and the adoption of a bourgeois conception of property. Although this offence disappeared at the end of the last century, the prohibition on the straying of domestic animals, and the separation of wild and domestic animals it represents—also at the basis of our modern law—remains. However, it may fade with the rise of ecological concerns and the emergence of environmental law, heralding a departure from the modern legal paradigm.